Spongioplasty with Dartos Flap Coverage in the Snodgrass Technique of Hypospadias Repair - Das, Sahadeb Kumar; Hasina, Kaniz; Huq, Md Ashraf Ul; Adil, Syed Abdul; Alam, Md Mahbubul; Alam, SM Shafiqul (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Objective: The aim of the study is to evaluate the role of spongiosal tissue with dartos flap coverage for preventing Urethrocutaneous Fistula (UCF) formation in the Snodgrass technique. Materials and Methods: It is a prospective study, performed on 35 patients of mid penile and distal hypospadias aged 15 months to 144 months who underwent urethroplasty in the Snodgrass technique using spongiosal tissue and dartos flap for neourethral coverage. Results: Among 35 patients, Age ranged from 15 months to 144 months (mean 85.94 months). Chordee was corrected by penile degloving alone in 11 patients, partial mobilization of urethral plate with spongiosum in 20 patients and 4 patients required dorsal plication. Glans groove was deep in 19 patients, shallow in 13 patients and no groove noticed in 3 patients. Sixteen patients had narrow urethral plate (<8mm) and 19 patients had adequate urethral plate (>8mm). Urethrocutaneous Fistula (UCF) was encountered in five patients (14.28%), meatal stenosis in two patients (5.71%), and partial glanular dehiscence in one patient. Conclusions: Approximation of spongiosal tissue along with dartos flap as the intermediate layer for neourethral coverage reduces fistula formation. J Bangladesh Coll Phys Surg 2020; 38(2): 64-67